Proses Kognitif Kompleks dalam Psikologi Pendidikan - Fauziah Nasution; Sehat Harahap; Ummi Kalsum; Adinda Fuadilah Alhumaira (Maktabatun: Jurnal Perpustakaan dan Informasi, 2022)
Learning is an activity related to cognitive processes. Cognitive processes are individual mental processes that can be understood as information processing. In educational psychology, cognitive processes are needed to explore students' complex mental processes. This study aims to find out how complex cognitive processes are in educational psychology. This study uses descriptive qualitative methods with data collection methods through literature studies by collecting various references regarding complex cognitive processes so that it can be concluded that matters relating to complex cognitive processes are about how conceptual and strategies introduce concepts and how the thinking process and its application in solution to problem.